Global talent retention : understanding employee turnover around the world - Allen, David G.; Vardaman, James M. (Talent management, 2021)
Retaining top talent is a universal concern that is increasingly global. However, the context, meaning, and mechanisms for changing jobs varies around the world. Global Talent Retention: Understanding Employee Turnover Around the World provides the first context-specific global perspective on retaining talent. Although extensive research informs understanding of why employees decide to leave or remain with organizations, the bulk of theory and research adopts a U.S.-centric perspective, problematic because most employees do not work for firms that are U.S.-owned or based. Global Talent Retention addresses the need for turnover theory and research to give more careful consideration to global and cross-cultural perspectives on employee retention, and includes contributions from a global range of scholars in differing cultural contexts in Africa, Asia, Europe, Latin America, and the Middle East. The chapters represent many of the largest and most dynamic economies in the world, including Bulgaria, China, Denmark, Germany, India, Mexico, South Africa, South Korea, Spain, Turkey, and the UK. Each -- Chapter provides a description of the institutional, legal, and cultural context as it relates to employee mobility, a review of context-specific research leading to a description of how the mechanisms of prominent turnover theories may operate differently in particular contexts, and the implications for research and practice related to employee turnover and retention.